The road ahead - Gates, Bill (New York, NY Viking, 1995)
he founder of Microsoft discusses how emerging technologies in the field of computer science are going to affect the future
D., 9/01
Keywords: Information superhighway--United States; Information technology--United States; Computer networks--United States; telecomunications--United States; Computer industry--United States